2003
DOI: 10.1097/00004728-200303000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular-Cholangiocarcinoma: Helical Computed Tomography Findings in 30 Patients

Abstract: The diagnosis of hepatocellular-cholangiocarcinoma should be considered when a hepatic tumor has CT features of both hepatocellular carcinoma and cholangiocarcinoma. Radiologists should be aware of this tumor type so that the biopsy is performed properly to allow sufficient tissue sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…On MRI, HCC, CC and combined tumors are typically moderately hyperintense compared with adjacent liver on T2-weighted imaging, with enhancement patterns similar to those seen by CT [ 11–16 ] . Additional findings seen in each of the three types of primary liver cancers include satellite nodules, biliary ductal dilation, portal or hepatic venous involvement and adenopathy [ 4 , 5 , 11 , 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, HCC, CC and combined tumors are typically moderately hyperintense compared with adjacent liver on T2-weighted imaging, with enhancement patterns similar to those seen by CT [ 11–16 ] . Additional findings seen in each of the three types of primary liver cancers include satellite nodules, biliary ductal dilation, portal or hepatic venous involvement and adenopathy [ 4 , 5 , 11 , 17 ] .…”
Section: Discussionmentioning
confidence: 99%
“…The cHCC-CC lesions resembling cholangiocarcinoma, however, enable low attenuation in the arterial phase and low, iso-or high attenuation in the venous phase [11] . Preoperatively cHCC-CC is, however, usually only considered when a liver tumor has CT features of both hepatocellular carcinoma and cholangiocellular carcinoma [12] . In addition, Toh et al [13] reported a hypodense tumor with vague contrast enhancement associated with elevation of α-fetoprotein levels and multiple regional lymphadenopathies as a cHCC-CC.…”
Section: Discussionmentioning
confidence: 99%
“…Such imaging patterns have been previously described by Fowler et al [12], who stated that peripheral arterial enhancement was the most common pattern observed in a combined tumor population. Aoki et al [13] and Ebied et al [14] also concluded that a common feature of combined HCC-CC tumors was target-like or reverse target-like enhancement. In this study, however, typical enhancement pattern of either HCC or CC, whichever major component was present in the combined tumor, was also observed.…”
Section: Discussionmentioning
confidence: 99%